The Academic Writing Challenges and Opportunities for Lecturer in Frame of MBKM Program During Covid-19 Pandemic - Herli Salim; Ima Ni'mah Chudari; Widjojoko Widjojoko; Muhammad Hanif (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This study aims at analyzing difficulties, identifying the support and needs of lecturers in academic writing, also lecturers’ perceptions toward the potential of the MBKM program to strengthen academic writing activities during the Covid-19 pandemic. This study employed a quantitative approach with historical survey methods and a descriptive study design. The data were collected utilizing multiple-choice questionnaires and descriptions along with Focus Group Discussions (FGD) activities. The subjects of this study were 45 lecturers from Universitas Pendidikan Indonesia (UPI) Serang Campus and Universitas Banten Jaya. The data were analyzed interactively based on theoretical propositions which were divided into 2 cases, namely opportunities and challenges with 4 aspects of discussion, such as difficulties, support, needs, and potential for the MBKM program. The results showed that most of the lecturers experienced difficulties in funding as well as the skills to express ideas and find suitable sources even though their productivity was still quite good. The institutional support in terms of funding and referral sources is still there however the number is decreasing. Nevertheless, language training and facilitation are prominently required. The lecturers’ need to support their academic writing activities is writing training and collaboration across departments as well as study programs. Their activeness in participating MBKM program correlates with their writing productivities also in lecturers’ exchange activities and collaborative research as well. The number and activities in academic writing need to be elevated to help productivity in academic writing during the Covid-19 pandemic. The MBKM program has the potential to accommodate these requirements.